Characterization of predictable quantum efficient detector at 488 nm and 785 nm wavelengths with an order of magnitude change of incident optical power. (22nd November 2021) - Korpusenko, Mikhail; Manoocheri, Farshid; Kilpi, Olli-Pekka; Varpula, Aapo; Kainlauri, Markku; Vehmas, Tapani; Prunnila, Mika; Ikonen, Erkki
Abstract: We investigate the predictable quantum efficient detector (PQED) in the visible and near-infrared wavelength range. The PQED consists of two n-type induced junction photodiodes with Al2 O3 entrance window. Measurements are performed at the wavelengths of 488 nm and 785 nm with incident power levels ranging from 100 µW to 1000 µW. A new way of presenting the normalized photocurrents on a logarithmic scale as a function of bias voltage reveals two distinct negative slope regions and allows direct comparison of charge carrier losses at different wavelengths. The comparison indicates mechanisms that can be understood on the basis of different penetration depths at different wavelengths (0.77 μm at 488 nm and 10.2 μm at 785 nm). The difference in the penetration depths leads also to larger difference in the charge-carrier losses at low bias voltages than at high voltages due to the voltage dependence of the depletion region.